ANALISIS EFEKTIFITAS MEDIA PROMOSI TERHADAP PENERIMAAN MAHASISWA BARU (PMB) - Bayu Dwi Raharja (Program Studi S1 Sistem Informasi Fakultas Komputer dan Teknik Universitas Alma Ata, 2021)
The level of competition for new student admissions at tertiary institutions in the Central Java region for the last 5 years is quite high. STMIK Sinar Nusantara has also experienced the impact of competition, which can be seen through the decline in new students by an average of 20% in the last 5 years. This study aims to determine how much influence the promotional media has on the acceptance of new students. By collecting data from questionnaires that have been distributed to 69 parents of STMIK Sinar Nusantara students. Where these students entered college from batch 2015, 2016, 2017, 2018 and 2019. The promotional media studied included print media, namely posters, brochures and billboards. And electronic media, namely radio and websites, as well as other media through daily conversations. After the data is tested for validity, reliability test and classical assumption are processed to produce a regression equation. Hypothesis testing shows that the three independent variables studied, namely the print media (X1), electronic media (X2) and other media (X3) variables, have a positive effect on the dependent variable, namely New Student Admissions (Y). Through variable X1, it has a coefficient value of 0.990, which means the effectiveness of print media has a positive influence on registrant interest (Y), as well as variables X2 and X3, each of which has a coefficient value of X2 = 0.787 and X3 = 0.626.